Tuberculosis: Searching for mycobacterium antigens inglomerull - Maita, Rosa (1996)
The aim of this work done at the Instituto de Patologia de la Facultad de Medicina-UNMSM was to know the frequency of secondary tuberculous glomerulonephritis, through a retrospective study of 42 autopsies and 3 post mortem biopsies in 45 tuberculous patients with glomerulonephritis. Mycobacterium antigens in renal glomeruli were identified by immunomicroscopy. The glomerular lesion was classified with the 1988 WHO classification of renal diseases. Clinical pathological correlation was done. We concluded : a) 37,78% of the cases in this study had Mycobacterium antigens positive in the glomeruli; b) In all the positive cases the glomerular lesion was classified as membranoproliferative or mesangiocapillary glomerulonephritis; c) Most of the patients with secondary mesangiocapillary glomerulonephritis had chronic pulmonary tuberculosis.